Da‘wah approaches in contemporary society - Shehu, Fatmir Mehdi (2019)
DIRECT: APPROACHES IN DAWAH through Words and expressions, which are used:(1). In lecturers, sermons, and day-to-day conversations and dialogues; (2) In printed media - writings and circulation of books, magazines and pamphlets; (3) In electronic media – TV, Radio, and internet – Face-Book, Blogs, You-tubes, WhatsApp, Skype, Messenger: (4) TO MAKE A CLEAR DISTINCTION BETWEEN ISLAM AND MUSLIMS - All these will help people to understand Islam INDIRECT APPROACHES IN DAWAH: through ACTIONS expressed through manners:- (1) Being a good example and a role model for others as a Muslim; (2) Bringing into practice the noble teachings of al-Din al-Islam; (3) Following the footsteps of the beloved Prophet (p.b.u.h.) in the day-to-day life; and (4) Being polite and gentle while acting and engaging with others.